2007
DOI: 10.1007/s00520-007-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral cryotherapy reduces mucositis and opioid use after myeloablative therapy—a randomized controlled trial

Abstract: Oral cryotherapy is an effective and well-tolerated therapy to alleviate mucositis and consequently reduce the number of days with i.v. opioids among patients treated with myeloablative therapy before BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 28 publications
(43 reference statements)
2
103
1
2
Order By: Relevance
“…The collective evidence was scored as level III. The RCTs, each with major flaws identified, found significant benefit for cryotherapy compared to no intervention or saline in two studies [18,22] and no benefit in the study conducted by Gori et al [17]. The remaining studies of lower evidence all reported improvement in mucositis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collective evidence was scored as level III. The RCTs, each with major flaws identified, found significant benefit for cryotherapy compared to no intervention or saline in two studies [18,22] and no benefit in the study conducted by Gori et al [17]. The remaining studies of lower evidence all reported improvement in mucositis.…”
Section: Resultsmentioning
confidence: 99%
“…The final set of 22 original reports and 2 metaanalyses was included in the final review (Table 1). A 23rd study [23] involving supplementary evaluation of data reported in 1 of the 22 publications [22] was also included. The two meta-analyses [24,25] were analyzed separately.…”
Section: Resultsmentioning
confidence: 99%
“…The treatments for oral mucositis includes: administration of topical antimicrobial agents [10], vitamins [11,12], growth factors [13,14], mouth washes [15], and cryotherapy [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmaların çoğunluğunda (n=12) hastaların oral mukozit düzeylerini değerlendirmek için DSÖ Oral Toksisite Skalası'nın kullanıldığı, diğer 6 çalışmada [3,6,8,22,28,29] ise farklı ağız değerlendirme ölçeklerinin kullanıldığı (NCI-CTC, RTOG Mukozit Değerlendirme Ölçeği, Eilers Ağız Değerlendirme Rehberi, Oral Mukozit Değerlendirme Ölçeği) saptanmıştır.…”
Section: Bulgularunclassified
“…Çalışmaların tamamında (%100) hastalarda çeşitli seviyelerde oral mukozit geliştiği saptanmıştır. Çalışmalar sonucunda hastalarda oral mukozit insidansında [4,5,6,7,8,26,28,29,30,31,32,33], oral mukozit şiddetinde azalma görüldüğü [6,8,22,24,26,27,28,32,33,34], oral mukozitin iyileşme sürecinin hızlandığı [6,24,33], oral mukozit ilişkili enfeksiyonlarda [2] ve hastane yatış süresinde azalma olduğu [2,7], ağrıyı azalttığı [2,5,28,34] ve opioid kullanımının azaldığı [29] ve yaşam kalitesinin arttığı [22] parenteral beslenme (TPN) kullanım süresinin kısaldığı [7] ve beslenme problemlerinin azaldığı [7,28] saptanmıştır.…”
Section: Bulgularunclassified